A study on regenerated zeolite adsorption capacity for ammonical nitrogen and COD removal from leachate - Ragunathan Santiagoo; Naimah Ibrahim; Faridah A.H. (Universiti Teknologi Mara (UiTM), 2008)
Organized by Organized by Universiti Teknologi Mara (UiTM) Cawangan Pulau Pinang, 8th - 9th December 2006 at UiTM Penang.